The Effect of Drought on Yield in Agriculture: 2020 Year Fatidic for Romania - Ana URSU; Ionut Laurentiu PETRE (Communications of International Proceedings, 2021)
In this paper we want to identify the effect that the severe drought registered in Romania in the agricultural year 2019-2020 had on the yield losses in agriculture. To develop this analysis, data on average yields per hectare extracted from national databases were used, as well as data on the level of precipitation extracted from international databases. Thus, following the analysis of the dynamics of average yields per hectare, precipitation and testing of hypotheses according to which the level recorded in 2020 is statistically significantly lower than in previous years. Thus, it was found that in the regions where the level of precipitation was higher, there were also increases in yields per hectare. Finally, following the running of the simple linear regression model, for the sunflower crop it was found that an increase in precipitation level by one unit will lead to an increase in yield by one kilogram and 260 grams of sunflower.
Keywords: drought; yield; agriculture; Romania; 2020.